Astronomy and Astrophysics in the Philosophy of Science - Anderl, Sibylle (2015)
This article looks at philosophical aspects and questions that modern astrophysical research gives rise to. Other than cosmology, astrophysics particularly deals with understanding phenomena and processes operating at "intermediate" cosmic scales, which has rarely aroused philosophical interest so far. Being confronted with the attribution of antirealism by Ian Hacking because of its observational nature, astrophysics is equipped with a characteristic methodology that can cope with the missing possibility of direct interaction with most objects of research. In its attempt to understand the causal history of singular phenomena it resembles the historical sciences, while the search for general causal relations with respect to classes of processes or objects can rely on the "cosmic laboratory": the multitude of different phenomena and environments, naturally provided by the universe. Furthermore, the epistemology of astrophysics is strongly based on the use of models and simulations and a complex treatment of large amounts of data.Comment: 14 pages, This is a draft of a chapter "Astronomy and Astrophysics'' that has been accepted for publication by Oxford University Press in the forthcoming book "The Oxford Handbook of Philosophy of Science'' edited by Paul Humphreys due for publication in May 201